HUBUNGAN ANTARA PELATIHAN, MOTIVASI DAN KETERSEDIAAN FASILITAS DENGAN PARTISIPASI JUMANTIK DI KOTA BLITAR - Dian Shanti Yunita (The Indonesian Journal of Public Health, 2016)
In Dengue Hemorrhagic Fever (DHF) is a health problem and the number of cases is increasing every year, including in East Java. Blitar City is one of the cities in East Java which is endemic dengue. The Incident Rate (IR) in 2015 which is 70,28 per 100.000 population over the target area that is 21 per 100.000 population. One effort that can be done to reduce the number of dengue cases is increasing activeness jumantik in the prevention of dengue. Jumantik task in the prevention of dengue fever include CHD (Flick Periodic Monitoring), larvasidasi and reporting results of CHD to the clinic regularly. The purpose of this study was to determine and analyze the relationship between training, motivation and availability of facilities with participation jumantik in Blitar City. This study used an analytic observational study with cross sectional study design. Respondents in this study are jumantik in Blitar City with a sample of 171 samples. The data used in this study are primary data and secondary data. Statistical test results obtained value of meaningful relationship training (p = 0,000), motivation (p=0,000) and the availability of facilities (p = 0,000).Conclusions of this research that thereare a relationship between the training, motivation and availability of facilities with participation jumantik in Blitar City. Suggestions for Blitar City Health Department and clinics in Blitar City which should jumantik training ongoing each year and monitor the results of CHD regularly to anticipate the incidence of DHF.Keywords: Blitar City, Jumantik, Participation